Implementasi Pembelajaran Tafsir Akhkam Melalui Lagu qur'any - Naelasari, Desy; An-nadhliyah, Khumairaoh (ILJ: Islamic Learning Journal, 2025)
Learning is a system that consists of an instructional system, namely components of messages, people, materials, equipment, techniques, and backgrounds or environments, which aim to bring students to understanding and as an effort to organize the environment to create teaching and learning conditions that are in accordance with Islamic teachings. , so that the learning that is obtained seems fun. This study aims to reveal and describe the implementation of Ahkam Tafsir learning through Qur'any Songs at the Bulurejo Islamic Boarding School, Diwek, Jombang. The type of research used in this research is field research, the approach used is qualitative which is descriptive in nature the design of data collection techniques through interviews, observation and documentation. the results of the study found that the planning of learning Tafsir Ahkam through qur'any songs included: formulating objectives, determining material, methods and media to support teaching and learning activities. The implementation of learning Tafsir Ahkam Through the Qur'any Song includes: first listening first, second being invited to sing together, third right on target, simple, practical. while the evaluation of learning Tafsir Ahkam Through Qur'any Songs includes: first for the recitation of Ba'da Subuh, namely there is no evaluation, but the ustadzah directly observes and gives questions to the students, so the ustadzah can already know it. Both Madrasah and Tarbiyah Final Level Santri are required to be able to memorize as a condition for taking a diploma.